Validation of the HIV risk perception scale (RPS-HIV) in men - Sánchez Medina, Ricardo; Lozano Quiroz, María Fernanda; Negrete Rodríguez, Oscar Iván; Enríquez Negrete, David Javier; Estrada Martínez, Maria de los Angeles (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2021)
The objective of this research was to develop and evaluate the psychometric properties of a scale aimed at measuring the perception of HIV risk in men. 1008 men with an average age of 31 years participated, half of them diagnosed with HIV. A scale in Likert format was designed and applied on the perception of risk for HIV transmission (EPR-HIV). The exploratory factor analysis yielded three factors, sexual risk practices, HIV transmission situations and safe sexual practices that together have an explained variance of 44.90 and an internal consistency of . 78; in addition, a concurrent validity was found between the scale and the consistency in the use of the condom. The results are discussed in terms of the importance of having valid and reliable instruments on risk perception of HIV in men.